PERSEPSI DAN PARTISIPASI STAKEHOLDER DALAM PENYUSUNAN RENCANA ZONASI WILAYAH PESISIR DI KABUPATEN JEPARA (STUDI KASUS: DESA BANDENGAN KECAMATAN JEPARA) - Pratiwi Rahmawati; M Mussadun (TATALOKA, 2017)
This study aims to assess the perceptions and participation of stakeholders in the preparation of the coastal areas zoning plan, with the goal of the research are: 1) Identify the different stages of the coastal areas zoning plan; 2) Identify coastal stakeholders; 3) To analyze the perceptions and participation of stakeholders in the preparation of the coastal areas zoning plan. The method in this research that use qualitative with in-depth interviews and observation. Sampling and analysis techniques using snowball sampling and interactive analysis by Miles and Huberman (1992). The results showed that the different stages of the coastal region zoning plan of Jepara changed to suit the latest regulations  Permen KP No. 23 Year 2016 concerning the planning management of coastal areas and small islands. Coastal stakeholders related to drafting a coastal region zoning plan of Jepara divided into three groups: the main stakeholder, stakeholder support, and key stakeholders. Perception and participation of major stakeholders based on the frequency of attendance, activity level, and the level of understanding can be categorized as "low". Instead, key stakeholders have the perception and participation based on the frequency of attendance, activity level, and the level of understanding that is categorized as "high." By contrast, supporters stakeholders have the perception and participation based on the frequency of attendance and the level of activity which is categorized as "high," but the level of understanding that is categorized as "medium."